2017
DOI: 10.1007/s10592-017-0951-9
|View full text |Cite
|
Sign up to set email alerts
|

An ecological role for assortative mating under infection?

Abstract: and outline how infection by pathogens or parasites might bring them about. We include a review of the empirical literature pertaining to disease-induced assortative mating. We also suggest future directions and methodological improvements that could advance our understanding of how the link between disease and mating patterns influences genetic variation and long-term population viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 97 publications
(120 reference statements)
0
9
0
Order By: Relevance
“…Many species use the MHC genotype of a potential partner, detected via pheromones, as the basis of mate choice behaviours (Campbell, Head, Wilfert, & Griffiths, 2017;Jordan & Bruford, 1998;Penn & Potts, 1999). The up-regulation of the olfactory receptor OR8D2 in frogs originating from positive disease history populations is therefore striking, particularly given that the ability to detect favourable MHC profiles in a mate is likely to be under stronger…”
Section: Up-regulated Genesmentioning
confidence: 99%
“…Many species use the MHC genotype of a potential partner, detected via pheromones, as the basis of mate choice behaviours (Campbell, Head, Wilfert, & Griffiths, 2017;Jordan & Bruford, 1998;Penn & Potts, 1999). The up-regulation of the olfactory receptor OR8D2 in frogs originating from positive disease history populations is therefore striking, particularly given that the ability to detect favourable MHC profiles in a mate is likely to be under stronger…”
Section: Up-regulated Genesmentioning
confidence: 99%
“…In contrast, we found a positive association between genome-wide similarity and breeding success, suggesting female koalas are more likely to produce offspring with males that are more genetically similar overall. A recent review showed mating with similar individuals can allow populations to adapt more quickly to virulent diseases and parasites ( Campbell et al, 2017 ). Assortative mate preferences may help protect koala populations from threatening infectious diseases such as chlamydia ( Polkinghorne, Hanger & Timms, 2013 ) and koala retrovirus ( Denner & Young, 2013 ), and should be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that, in some circumstances, carrying multiple copies of the same MHC allele allows for higher disease resistance ( Grimholt et al, 2003 ; Nuismer, Otto & Blanquart, 2008 ). However, MHC assortative mating may make populations more vulnerable to future disease outbreaks or other stochastic events ( Campbell et al, 2017 ). We suggest that female koalas might not solely choose more-similar mates but may rather optimize the quantity and combination of MHC alleles in the offspring (see also Milinski, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that, in some circumstances, carrying multiple copies of the same MHC allele allows for higher disease resistance (Grimholt et al 2003;Nuismer et al 2008). However, MHC assortative mating may make populations more vulnerable to future disease outbreaks or other stochastic events (Campbell et al 2017). Therefore, we suggest that female koalas may not solely choose more-similar mates but may rather optimise the quantity and combination of MHC alleles in the offspring (see also Milinski 2006).…”
Section: Genetic Determinants Of Koala Mate Choicementioning
confidence: 89%
“…In contrast, we found a positive association between genome-wide similarity and breeding success, suggesting female koalas are more likely to produce offspring with males that are more genetically similar overall. A recent review highlighted how mating with similar individuals can allow populations to adapt more quickly to virulent diseases and parasites (Campbell et al 2017). Assortative mate preferences may therefore help protect koala populations from threatening infectious diseases such as chlamydia and koala retrovirus, and should be examined further.…”
Section: Genetic Determinants Of Koala Mate Choicementioning
confidence: 99%